Co-valorization of Tuff and Sandy Residues in Roads Construction - Hassan Moulay Omar; Rachid Zentar; Mustapha Akacem; Belkacem Mekerta; Mohamed Mouli (Salehan Institute of Higher Education, 2022)
In recent years, the use of local materials in pavements has developed to compensate for the lack of normalized standard materials in the Algerian arid regions. The main objective of this research is to assess the co-valorization of two local materials to design a road material with satisfactory characteristics. In this context, the use of tuff in combination with sand residues is explored. The evolution of the characteristics of tuffs mixed with sand residues according to percentages ranging from 0% to 50% is highlighted. The used materials were subjected to physical and mechanical tests. Then, a series of mechanical tests were carried out on mixed samples compacted at the optimal characteristics that were deduced from the modified Proctor test. The obtained results highlight the existence of an optimal formulation composed of 70% tuff and 30% sandy residues, which presented an unconfined compressive strength (UCS) of 5.16 MPs and a CBR index (CBRI) of 42.6 %. Moreover, the results show clearly the evolution of the measured characteristics with time (drying) and without the addition of binders. The possibility of the use of studied mixtures in pavements has been verified regarding the recommendations in use (CTTP 2001) and the Saharan Road Technique (SRT). Doi: 10.28991/CEJ-2022-08-05-013 Full Text: PDF